1995
DOI: 10.1029/95gl03314
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of high velocity anomalies in the transition zone associated with Southern Kurile Subduction Zone

Abstract: We address the use of regional broad‐band waveform data to better constrain the upper mantle transition zone structure. We then show evidence of high velocity anomalies in the transition zone associated with the southern Kurile subduction zone. Modeling of the triplicated regional waveforms supports that high velocity anomalies exist in the deeper part of the transition zone (over 500 km in depth), and the “660” discontinuity may be depressed to about 690 km depth. Our results suggest there is some degree of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 9 publications
4
37
0
Order By: Relevance
“…Published models, however, show variable structures at transition zone depths in subduction regimes, and there is still debate as to whether sub ducting slabs penetrate into the lower mantle [Creager and Jordan, Figure 1). However, P wave travel times from the ISC catalog have poor sampling of the deeper part of the transition zone (...550 km to the 660 km discontinuity) because no first-arriving P waves bottom in that depth range because of the triplication caused by the discontinuity [Tajima and Grand, 1995]. Accordingly, some of the features suggested by the tomographic models are still inconclusive.…”
Section: Introductionmentioning
confidence: 89%
“…Published models, however, show variable structures at transition zone depths in subduction regimes, and there is still debate as to whether sub ducting slabs penetrate into the lower mantle [Creager and Jordan, Figure 1). However, P wave travel times from the ISC catalog have poor sampling of the deeper part of the transition zone (...550 km to the 660 km discontinuity) because no first-arriving P waves bottom in that depth range because of the triplication caused by the discontinuity [Tajima and Grand, 1995]. Accordingly, some of the features suggested by the tomographic models are still inconclusive.…”
Section: Introductionmentioning
confidence: 89%
“…Such changes in seismic structure in the transition zone should affect triplicated waveforms at regional distances, but the depth range near the discontinuity can be strongly sampled only by secondary arrivals. Tajima and Grand (1995) thus analyzed regional broadband P waveforms in the frequency Fig. 3.…”
Section: Implication Of Anomalies By Waveform Modelingmentioning
confidence: 99%
“…Analysis of triplicated waveforms has so far been mostly applied to deep events (Tajima and Grand, 1995;Tajima et al, 2009), in order to separate the influence of the discontinuities from the depth phases. We have shown that shallow events can be modelled when source parameters are carefully estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling of individual triplicated waveforms has been successfully used to sample localized heterogeneities in the MTZ (Tajima and Grand, 1995;Melbourne and Helmberger, 2002;Tajima et al, 2009). A few studies that included picked arrival times into ray theoretical inversions demonstrated the potential of triplicated waves for tomography (Grand, 2002), but so far they have rarely been used.…”
Section: S C Stähler Et Al: Finite-frequency Measurements Of Triplmentioning
confidence: 99%